Principles of economics (New York : McGraw-Hill ; Cambridge, MA : MathSoft, 1991)
Tool for learning the mathematics of micro- and macro- economics. Includes MathCAD technical calculation software.
Title from disk label.
Production level cataloging.
System requirements: 386/486 PC or compatible; Windows 3.1 or higher.
Keywords: Economics -- Outlines, syllabi, etc